SEXUAL ABUSE AND REHABILITATION OF VICTIMS: PUBLIC HEALTH IMPLICATIONS - ISIJOLA Bukola Ibiso; JEMILUGBA Magreth O (CV. ADIBA AISHA AMIRA, 2025)
Sexual abuse is a global issue. All genders are affected, both young and old, most especially the girl child. As a major issue in public health, sexual assault affects millions of individuals annually. In addition to causing physical harm, it also has a significant effect on people's mental and psychological well-being. There are both short-term and long-term effects linked to an elevated risk of various sexual and reproductive health issues. Individuals may be stigmatized and ostracized by their families and communities when abused, hence, parents and guardians should create time for their children and monitor all activities they engage in. There should be implementation of capital punishment for offenders and laws should be put in place to protect the girl child. When it comes to medical and psychological treatment for victims of sexual assault, as well as evidence collection to aid prosecutions, health professionals play a significant role.